Inosine: biofunctions and the roles in human diseases - Li, Fangwei; Zhang, Jiawen; Kang, Jiayi; Tong, Xuemei; Zhang, Ping; Zhu, Yemin (Frontiers in Endocrinology, 2025)
Inosine, a basic component of purine nucleotide, is mainly seen only as a building block in nucleotide synthesis. It is also a versatile bioactive molecule with diverse biofunctions. These biofunctions are strongly related to human diseases or pathological conditions, such as cancer, obesity, inflammation, neurodegenerative diseases, and autoimmune diseases. In this article, we will discuss the roles and functions of inosine in a wide array of human diseases, targeting metabolism modulation, purinergic signaling, and RNA editing. We will also mention its great importance as a biomarker of human diseases. We believe that a more thorough understanding of inosine and its intricate roles in various human diseases could inspire future therapeutic methods or preventive modalities for these diseases.